Innovating Pre-service Science Teachers’ Professional Development with Virtual Reality (International Conference on Computers in Education, 2020)
As the need for authentic experiences has increased in the science education for 21st century learners, there has been more attention placed on the modes of instruction that can supply greater realism and immersion. In this light, the use of virtual reality (VR) has received considerable attention. I aim to conduct design-based research on novel approaches that support the professional development of pre-service science teachers based upon learning theories. I will also conduct experimental studies and case studies in order to have more in-depth investigation of the roles of VR and pedagogical scaffolds on improving the effectiveness of the professional development. Ethnographic or case studies will also be conducted to have a more comprehensive understanding of the pre-service science teachers’ attitudes, perceptions, challenges, and expectations with regard to the VR integrated professional development method.